Bank interest margin, multiple shadow banking activities, and capital regulation - Jyh-Horng Lin; Shi Chen; Fu-Wei Huang (International Journal of Financial Studies, 2018)
In this paper, we develop a contingent claim model to evaluate a bank's equity and liabilities that integrates the premature default risk conditions with loan rate-setting behavioral mode and multiple shadow banking activities under capital regulation. The barrier options theory of corporate security valuation is applied to the contingent claims of a bank. The barrier reports that default can occur at any time before the maturity date. We focus on a type of earning-asset portfolio, consisting of balance-sheet banking activities of loans and liquid assets and shadow banking activities of wealth management products (WMPs) and entrusted loans (ELs). The optimal bank interest margin, i.e., the spread between the loan rate and the deposit rate, is derived and analyzed. The results provide an alternative explanation for the decline in bank interest margins, which better fits the narrative evidence on bank spread behavior under capital regulation in particular during a financial crisis. Raising either WMPs or ELs leads to a transfer of wealth from equity holders to the debt holders, and hence increases the deposit insurance liabilities. We also show that the multiple shadow banking activities of WMPs and ELs captured by scope equities may produce superior return performance for the bank. Tightened capital requirements may reinforce the superior return performance by a surge in shadow banking activities that makes the bank less prudent and more prone to risk-taking at a reduced margin, thereby adversely affecting banking stability. We demonstrate that financial disturbance may be created because of the potential for shadow banking activities to spill over to regular banking activities and damage the real economy.
Keywords: G01; G21; G28; 330; wealth management products; entrusted loans; bank interest margin; capital regulation